2021
DOI: 10.1038/s41467-021-21399-7
|View full text |Cite
|
Sign up to set email alerts
|

Emergent vulnerability to climate-driven disturbances in European forests

Abstract: Forest disturbance regimes are expected to intensify as Earth’s climate changes. Quantifying forest vulnerability to disturbances and understanding the underlying mechanisms is crucial to develop mitigation and adaptation strategies. However, observational evidence is largely missing at regional to continental scales. Here, we quantify the vulnerability of European forests to fires, windthrows and insect outbreaks during the period 1979–2018 by integrating machine learning with disturbance data and satellite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
133
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(136 citation statements)
references
References 70 publications
3
133
0
Order By: Relevance
“…It is thus fundamental to recognize the role of biological legacies left by disturbances [15], since they can strongly influence both the post-disturbance recovery pattern [16,17] and the residual provision of ecosystem services through their type, number, and spatial arrangement. Regarding windstorms, the main disturbance affecting European forests [13,[18][19][20], the main structural legacies that are present on a windthrown site are lying logs, stumps and snags, or snapped trees. After the Vivian storm in Switzerland, it was observed that the presence of deadwood could have a positive effect in scattering the energy of falling blocks, due to an increase of terrain roughness [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus fundamental to recognize the role of biological legacies left by disturbances [15], since they can strongly influence both the post-disturbance recovery pattern [16,17] and the residual provision of ecosystem services through their type, number, and spatial arrangement. Regarding windstorms, the main disturbance affecting European forests [13,[18][19][20], the main structural legacies that are present on a windthrown site are lying logs, stumps and snags, or snapped trees. After the Vivian storm in Switzerland, it was observed that the presence of deadwood could have a positive effect in scattering the energy of falling blocks, due to an increase of terrain roughness [21].…”
Section: Introductionmentioning
confidence: 99%
“…The quick succession of abiotic and biotic stresses can further worsen forest damage. A quantification of the vulnerability of European forests to windthrows (40% of losses), fires (34%), and insect outbreaks (26%) during the period 1979-2018 revealed that about 33.4 billion tons of forest biomass were seriously affected by these disturbances (Forzieri et al, 2021). There is a clear trend toward higher overall forest vulnerability driven by a warming-induced reduction in plant defenses against insect outbreaks, especially at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Climate models predict temperature to rise another 0.9-3.5 • C until 2100 (climate models in Table 1 for Europe). While for Northern Europe temperature will continue to rise drastically, for Southern Europe a further reduction of summer precipitation will probably have more severe consequences [1,4]. Forests react to climate change not gradually but rather suddenly in response to climatic extremes [5,6].…”
Section: Introductionmentioning
confidence: 99%